2017
DOI: 10.1007/s11417-017-9255-8
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Wildlife Trafficking: Three Case Studies Involving Asia

Abstract: As wildlife trafficking or the illegal wildlife trade has taken a more prominent place on the global agenda, discussions are taking place as to how wildlife trafficking happens. An increased understanding has revealed that corruption is a key facilitator of this profitable and pervasive global black market, but limited research has explored exactly what that corruption looks like and how corruption enables wildlife to be trafficked. Furthermore, research shows that Asia, particularly China and Southeast Asia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 23 publications
0
51
0
1
Order By: Relevance
“…Some studies have suggested that the existence of legal international trade enables the illegal trade in wild-caught animals [30,31]. For example, a legal quota system may facilitate illegal trade through deliberate or accidental misidentification of species and false permits [32,33]. Despite the international crisis, designation, regulation, and enforcement efforts still remain insufficient to effectively control this illicit trade [34] (p. 1), and with a globalised market driving demand, it continues to rapidly increase [17] (p. 2).…”
Section: Illegal Wildlife Tradementioning
confidence: 99%
“…Some studies have suggested that the existence of legal international trade enables the illegal trade in wild-caught animals [30,31]. For example, a legal quota system may facilitate illegal trade through deliberate or accidental misidentification of species and false permits [32,33]. Despite the international crisis, designation, regulation, and enforcement efforts still remain insufficient to effectively control this illicit trade [34] (p. 1), and with a globalised market driving demand, it continues to rapidly increase [17] (p. 2).…”
Section: Illegal Wildlife Tradementioning
confidence: 99%
“…Stockpiles function as a buffer for lean periods and can also be used for speculation purposes (‘t Sas‐Rolfes, Moyle, & Stiles, 2014; Mason, Bulte, & Horan, 2012). Operators and traffickers can leverage stockpiles to take advantage of legal loopholes favoring sourcing and trading of products (Vandergrift, 2013), which can manifest in adaptation to political changes and market conditions facilitating illegal trafficking (Challender & MacMillan, 2014; Hall, Milner‐Gulland, & Courchamp, 2008; Wyatt, Johnson, Hunter, George, & Gunter, 2018). Market condition fluctuations can influence the flow of traded goods.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, illicit trade is carried out through practices that can enable pathogens to jump between species. For instance, wild-caught animals are bundled in consignments carrying similarly looking captive breds (Wyatt et al, 2018). The close contact between animals can enable the spread of pathogens from wild-caught to captive breds.…”
Section: Introductionmentioning
confidence: 99%